2012
DOI: 10.1039/c2dt31106b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quinoline as a remote sensitiser for red and near-infrared emissive lanthanide(iii) ions in solution and the solid state

Abstract: In order to evaluate quinoline as a remote sensitiser, we have prepared a DTPA based ligand, H3L, bearing quinoline bisamide arms for the complexation of a range of lanthanide(III) ions to give the neutral complexes LnLwhere Ln(3+) = Y(3+), Eu(3+), Sm(3+), Tb(3+), Er(3+), Yb(3+), Nd(3+), Gd(3+). Detection of the phosphorescence signal exhibited by the GdLcomplex at 77 K confirmed that the triplet energy level of the sensitiser at 21,190 cm(-1) was suitable for the indirect population of a range of lanthanide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 53 publications
(79 reference statements)
2
11
0
Order By: Relevance
“…2 F 7/2 transition of Yb 3+ ion. This band splits into two bands centered 980, 1022 nm in 6 and at 985, 1005 nm in 11, which result from the ligand-field effect [51][52][53][54]. The absence of the ligand-based emission in the emission spectra of 2, 3, 4, 6, 7, 8, 9 and 11 suggests that the energy transfer from the ligand to the lanthanide center is more effective.…”
Section: Luminescent Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…2 F 7/2 transition of Yb 3+ ion. This band splits into two bands centered 980, 1022 nm in 6 and at 985, 1005 nm in 11, which result from the ligand-field effect [51][52][53][54]. The absence of the ligand-based emission in the emission spectra of 2, 3, 4, 6, 7, 8, 9 and 11 suggests that the energy transfer from the ligand to the lanthanide center is more effective.…”
Section: Luminescent Propertiesmentioning
confidence: 92%
“…It is red-shifted about 52 nm compared with the ligand due to both the deprotonation of carboxylic acid and the coordination action of carboxylate groups to metal centers [49,50]. The other broad emission band at 546 nm is phosphorescence [51]. Upon excitation at 330 nm, compounds 2 and 7 ( Fig.…”
Section: Luminescent Propertiesmentioning
confidence: 95%
“…Bisamides of diethylenetriamino-N,N',N''-pentaacetic acid (DTPA), containing quinoline derivatives as amino component functioning as light harvesting fluorophore antenna, were used as polidentate ligands of H 3 L 2 and H 3 L 3 types for the synthesis of complexes with a number of Ln III ions. 250,251 Complexes with composition LnL 2 (322a-h) were obtained on the basis of ligands H 3 L 2 (Scheme 26) and is was shown that 6-aminoquinoline acts as a remote sensitizer for Ln-ions. 250 All compounds were characterized by mass spectra, and diamagnetic complex 322a was studied by 1 H NMR spectroscopy.…”
Section: V2 Complexes With Rare Earth Elementsmentioning
confidence: 99%
“…250,251 Complexes with composition LnL 2 (322a-h) were obtained on the basis of ligands H 3 L 2 (Scheme 26) and is was shown that 6-aminoquinoline acts as a remote sensitizer for Ln-ions. 250 All compounds were characterized by mass spectra, and diamagnetic complex 322a was studied by 1 H NMR spectroscopy. The photophysical analysis of complexes showed that compounds Eu (322b) and Sm (322c) possess red emission, complexes Er, Yb, Nd (322e-g) emitted in near IR range (900−1500 nm) in powders and solutions.…”
Section: V2 Complexes With Rare Earth Elementsmentioning
confidence: 99%
“…[10][11][12] However, like all lanthanide ions, Tb(III) must be excited indirectly via non-radiative energy transfer as f-f transitions themselves are Laporte forbidden, 13 giving rise to weak molar extinction coefficients (typically 1-10 M −1 cm −1 ) for the free unbound ions. 14 Therefore Tb(III) luminescence must be mediated by a polydentate-based ligand, in which the organic moiety chelates the lanthanide centre excluding water molecules in the first coordination sphere to the greatest extent, 15 as well as incorporating organic chromophores for transferring energy, utilizing the so-called 'antenna effect'. [16][17][18][19] Several lanthanide containing species, normally Eu(III) complexes or the generally more luminescent Tb(III) systems, have been employed as pH dependent molecular switches.…”
Section: Introductionmentioning
confidence: 99%